Eminent Maricones Arenas, Lorca, Puig, and Me - Manrique, Jaime (The University of Wisconsin Press, 2001)
Jaime Manrique weaves into his own memoir the lives of three important twentieth-century Hispanic writers: the Argentine Manuel Puig, author of Kiss of the Spider Woman; the Cuban Reinaldo Arenas, author of Before Night Falls; and Spanish poet and playwright Federico García Lorca.